(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
In this contribution, new data concerning lichen-forming and lichenicolous fungi in Ukraine are presented. It includes new records, exclusions, and confirmations to the Ukrainian administrative regions or taxa in the genera of Arthonia, Aspicilia, Aspiciliella, Bacidia, Buellia, Cercidospora, Circinaria, Cladonia, Clypeococcum, Codonmyces, Didymellopsis, Didymocyrtis, Heterocephalacria, Laetisaria, Lambiella, Lecanora, Lepraria, Lichenochora, Lichenoconium, Lichenostigma, Lichenothelia, Marchandiomyces, Montanelia, Phaeospora, Placynthiella, Polycoccum, Protoparmeliopsis, Pyrenochaeta, Pyrenodesmia, Pyrenopsis, Refractohilum, Rinodina, Rosellinula, Scytinium, Sphaerellothecium, Sphinctrina, Staurothele, Stigmidium, Taeniolella, Thallinocarpon, Toninia, Trapelia, Weddellomyces, Xanthoparmelia and Xanthoriicola. Among them 28 species of lichen-forming and lichenicolous fungi are new to Mykolaiv region, 21 species new to Dnipropetrovsk region, 17 species new to Cherkasy region, 7 species new to Kherson region, 5 species new to Zaporizhzhia region, 3 species new to Chernivtsi region, 3 species new to Odessa region, 3 species new to Luhansk region, 2 species new to Donetsk region, 2 species new to Kirovograd region, one species new to Ternopil region and one species new to Rivne region. Caloplaca xerica is a new host species for Lichenochora caloplacae. In Ukraine, Aspicilia cinerea is a dubious species and it needs to be removed from lichen list of Cherkasy, Donetsk, Dnipropetrovsk, Kirovograd, Mykolaiv and Zaporizhzhia regions. Lepraria neglecta was erroneously reported for Donetsk, Mykolaiv and Zaporizhzhia regions and should be removed from the species lists of these regions. Miriquidica complanata is erronoeusly reported for Zaporizhzhia regions and should be excluded from the list of this region.